Influence of the Location of Electron-Donating 3,4-Ethylenedioxythiophene (EDOT) Moiety in the A–π–D–π–A Type Conjugated Molecules on the Optoelectronic Properties and Photovoltaic Performances - Wang, Lilei; Zhang, Ying; Guan, Xiang; Gao, Wei; Lin, Yi; Luo, Qun; Tan, Hongwei; Yang, Hai-Bo; Ma, Chang-Qi (Organic Materials, 2021)
A–π–D–π–A type conjugated small molecules play an indispensable role in organic photovoltaics. Understanding the relationship between the molecular structure and performance is a fundamental question for the further rational design of high-performance organic materials. To red-shift the absorption spectrum of benzo[1,2-b:4,5-b']dithiophene (BDT) based A–π–D–π–A type compounds, an electron-donating 3,4-ethylenedioxythiophene (EDOT) moiety was introduced into the π-conjugation bridge unit. Two new compounds with EDOT next to the central BDT core (COOP-2HT-EDOT-BDT) or next to the terminal electron acceptor unit (COOP-EDOT-2HT-BDT) were synthesized and characterized. The compound COOP-2HT-EDOT-BDT showed higher molar extinction coefficient (εabsmax = 1.06 × 105 L mol−1 cm−1), lower optical band gap (Eg = 1.56 eV) and high HOMO energy level (EHOMO = −5.08 eV) than COOP-EDOT-2HT-BDT (εabsmax = 0.96 × 105 L mol−1 cm−1, Eg = 1.71 eV, EHOMO = −5.26 eV), which is attributed to the intensive interaction between the EDOT unit and the HOMO orbital, as confirmed by the theoretical calculation results. However, the higher power conversion efficiency of 3.58% was achieved for the COOP-EDOT-2HT-BDT:PC61BM-based solar cells, demonstrating that the electron-donating EDOT unit adjacent to the electron-withdrawing end-capped group (COOP) is a better way to achieve high-performance photovoltaic materials.
Keywords: organic solar cells; organic semiconductors; A–π–D–π–A small molecules; benzo[1,2-b:4,5-b′]dithiophene derivatives; 3,4-ethylenedioxythiophene